Measuring human resources’ value using human resources accounting methods and models- Theoretical study- (El-Wahat Journal for Research and Studies, 2020)
This article aims to identify the role of human resources accounting methods and models in measuring human resources’ value, by showing different concepts human resources accounting its importance and objectives in a fast-changing environment, and its historical evolution, and the most important methods and models to measure human resources’ value as Historical cost, Present value, opportunity Cost, Replacement Cost, The Lev & Schwartz, and Hermenson.In this article we have reached a set of results, human resources accounting gather all the human resource operations costs and capitalize it in the assets of the organization, and by this, it will gain loyalty of its human resources. Organizations have to measure its human resources in order to get an eye to their situations and their competencies. And the financial information about human resources are very important to the organization and it is a key element in order to take right decisions.Key words: accounting, human resources, human resources accounting, measurement, value.